The Influence of Performance Expectations, Knowledge of Accounting Software, and Business Expectations on MSMEs Profitability Using Cloud Accounting as a Moderator Variable (MSMEs In Bandar Lampung City) - Vanessa Gabriela; Andala Rama Putra Barusman (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the influence of performance expectation variables, knowledge of accounting software, and business expectations on profitability mediated by cloud accounting. This type of research is quantitative research with primary data from respondents through questionnaire data collection using Google Form. The population in this study was 30 MSMEs domiciled in Bandar Lampung City. Data is analyzed using PLS-SEM in the SmartPLS 4 application. Based on the research results, Performance Expectations have a significant positive effect on profitability, while business Expectations and Knowledge of Accounting Software do not have a significant positive effect on profitability. In addition, Performance Expectations and Knowledge of Accounting Software have a significant positive effect on profitability through the use of cloud accounting, while Business expectations do not have a significant positive effect on profitability through the use of cloud accounting, and Performance Expectations and Knowledge of Accounting Software have a significant positive effect of cloud accounting, while Business Expectations do not have a significant positive effect of cloud accounting.